Henry Pelham Holmes Bromwell papers - Bromwell, Henry Pelham Holmes, 1823-1903.
Thirty-one bound volumes of correspondence and autographs, index to the volumes, financial papers, and other papers relating chiefly to Bromwell's years as U.S. representative from Illinois. Includes material concerning Bromwell's father, Henry Broughton Bromwell, and his daughter, Henrietta E. Bromwell. Correspondents include Salmon P. Chase, George William Childs, Jefferson Davis, Ninian Edwards, James R. Gilmore, O.M. Hatch, Robert Green Ingersoll, Abraham Lincoln, Richard James Oglesby, Ida M. Tarbell, and Lyman Trumbull.
Lawyer, editor, and U.S. representative from Illinois.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bromwell, Henrietta E; Bromwell, Henry Broughton; Chase, Salmon P. -- 1808-1873 -- Correspondence; Childs, George William, -- 1829-1894 -- Correspondence; Davis, Jefferson, -- 1808-1889 -- Correspondence; Edwards, Ninian, -- 1775-1833 -- Correspondence; Gilmore, James R. -- 1822-1903 -- Correspondence; Hatch, O. M. -- 1814-1893 -- Correspondence; Ingersoll, Robert Green, -- 1833-1899 -- Correspondence; Lincoln, Abraham, -- 1809-1865 -- Correspondence; Oglesby, Richard J. -- 1824-1899 -- Correspondence; Tarbell, Ida M. -- 1857-1944 -- Correspondence; Trumbull, Lyman, -- 1813-1896 -- Correspondence; Illinois -- History; Illinois -- Politics and government; United States -- Politics and government -- 19th century; Representatives, U.S. Congress -- Illinois